PENGARUH PERSONAL BRANDING TERHADAP PENGEMBANGAN KARIER DIGITAL (SEBUAH STUDI LITERATUR) - Mihardianto; Arma Putra, Febi; Jaya, Nurman (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2026)
The purpose of this study is to identify various personal branding strategies that can be applied to career development in the digital era, to understand their benefits for enhancing individual professionalism, and to analyze the influence of personal branding on career opportunities. This research employs a qualitative approach using the library research method, which involves collecting and reviewing relevant academic literature. The findings reveal that key strategies in building personal branding include defining one’s identity, developing professional networks, and maintaining a consistent personal image. Personal branding enables individuals to craft a unique narrative that distinguishes them from others and builds professional appeal in the digital world. A strong personal reputation can open doors to new opportunities such as job offers, business collaborations, and strategic partnerships. Furthermore, personal branding plays an important role in expanding professional networks with individuals who share similar interests and career goals.